Death orders the vanguard of modern terrorism in revolutionary Russia - Geifman, Anna 1962-
Explores psychological incentives for aggressive behavior and ideologically motivated hostility, as they evinced themselves in the early 20th-century Russian political setting, and poses questions related to the universality of contemporary terrorist practices and to apply psychohistorical means of inquiry to modern and postmodern terrorism in various parts of the world, particularly the Middle East